Crowdfunding's Potential for the Developing World - World Bank (Washington, DC, 2014)
Crowdfunding is an Internet-enabled way for businesses or other organizations to raise money in the form of either donations or investments from multiple individuals. This new form of capital formation emerged in the wake of the 2008 financial crisis largely because of the difficulties faced by artisans, entrepreneurs and early-stage enterprises in raising funds. Crowdfunding takes advantage of crowd-based decision-making and innovation, and applies it to the funding of projects or businesses. Using social networks, social profiles, and web-based communication, individuals and companies have raised billions of dollars in debt, equity, and donations for projects. Building a crowdfunding ecosystem depends on key enablers to build trust. This document explores specific strategies to drive crowdfunding, the risks in crowdfunding and how to mitigate them, and the potential use of crowdfunding in the developing world.